2016
DOI: 10.1002/ana.24620
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Imaging of Individual Remyelination Profiles in Multiple Sclerosis

Abstract: BackgroundQuantitative in vivo imaging of myelin loss and repair in patients with multiple sclerosis (MS) is essential to understand the pathogenesis of the disease and to evaluate promyelinating therapies. Selectively binding myelin in the central nervous system white matter, Pittsburgh compound B ([11C]PiB) can be used as a positron emission tomography (PET) tracer to explore myelin dynamics in MS.MethodsPatients with active relapsing‐remitting MS (n = 20) and healthy controls (n = 8) were included in a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 208 publications
(126 citation statements)
references
References 41 publications
5
119
1
1
Order By: Relevance
“…This theory was previously suggested by the observations in post-mortem tissue that a subset of multiple sclerosis patients exhibited more than 80% of their lesions remyelinated (Patrikios et al , 2006). Recently, the concept of good or bad ‘remyelinator’ was also supported by the dynamic imaging of remyelination patterns among multiple sclerosis patients (Bodini et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory was previously suggested by the observations in post-mortem tissue that a subset of multiple sclerosis patients exhibited more than 80% of their lesions remyelinated (Patrikios et al , 2006). Recently, the concept of good or bad ‘remyelinator’ was also supported by the dynamic imaging of remyelination patterns among multiple sclerosis patients (Bodini et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…An endogenous myelin repair occurs in some patients (Bramow et al , 2010) but remyelination extent and efficacy is highly variable among patients and this variability is not linked to age, disease duration, or clinical forms of the disease (Patani et al , 2007). A recent longitudinal follow-up of newly formed demyelinated lesions—using PET and MRI combined with myelin specific markers—documented a large interindividual heterogeneity of remyelination (Bodini et al , 2016). Interestingly, the remyelination index was inversely correlated with clinical disability, a result confirming that myelin repair is essential to slower disease evolution.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, may be largely a technical issue, as a diffusion tensor approach did show a spatial association between GM atrophy and adjoining diffuse WM damage (Bodini et al, 2009). The latter finding was later confirmed longitudinally (Bodini et al, 2016), and it was suggested that WM damage causes GM atrophy more so than the other way around. While this may certainly be true, second-order effects may start playing a role in later disease stages.…”
Section: Neuroimagingmentioning
confidence: 86%
“…PET studies on MS have focused on evaluating microglial activation using the 18 kDa translocator protein (TSPO) ligands, and on developing ways to assess remyelination. 5 In this topical review, we describe the advances made in imaging microglial activation in the field of MS, and discuss its challenges and future prospects.…”
Section: Introductionmentioning
confidence: 99%